Safety and efficacy of digital chest drainage units compared to conventional chest drainage units in cardiac surgery. (6th April 2020) - Saha, Shekhar; Hofmann, Sandra; Jebran, Ahmad Fawad; Waezi, Narges; Kutschka, Ingo; Friedrich, Martin G; Niehaus, Heidi
Abstract: OBJECTIVES: The use of digital chest drainage units (CDUs) has become increasingly common in thoracic surgery due to several advantages. However, in cardiac surgery, its use is still limited in favour of conventional analogue CDUs. In order to investigate the potential benefit of digital CDUs in cardiac surgery, we compared the safety and efficacy of both systems in patients undergoing cardiac surgery at our centre. METHODS: We retrospectively investigated 265 consecutive patients who underwent cardiac surgery at our institution between June 2017 and October 2017. These patients were divided into 2 groups: patients with analogue (A, n  = 65) and digital CDUs (D, n  = 200). Postoperative outcome was analysed and compared between both groups. In addition, the 'user experience' was evaluated by means of a questionnaire. RESULTS: The median age of the cohort was 70 years ( P  = 0.167), 25.3% of patients were female ( P  = 0.414). There were no differences in terms of re-explorative surgery or use of blood products. Nor was there a difference in the overall amount of fluid collected. However, during the first 6 h, more fluid was collected by the digital CDUs. The overall rate of technical failure was 0.4%. We observed a significantly higher rate of clotting in the tubing system of the digital CDUs ( P  = 0.042). Concerning the user experience, the digital CDUs were associated with a more favourable ease of use on the regular wards ( P  < 0.001). With regard to the overall user experience, the digital CDUs outperformed the analogue systems ( P  = 0.002). CONCLUSIONS: Digital CDUs can be safely and effectively applied in patients after cardiac surgery. Due to the improved patient mobility and simplified chest tube management, the use of digital CDUs may be advantageous for patients after cardiac surgery. However, the issue of clotting of the tubing systems should be addressed by further technical improvements.